Population structure and some growth properties of chub Squalius cephalus (Linnaeus, 1758) in Devres Stream of Kızılırmak River, Turkey - Semra Benzer; Ali Gül (Journal of Fisheries, 2017)
This study describes the population structure, growth and condition factor of chub (Squalius cephalus) in Devres Stream of Kızılırmak River caught between June 2010 and June 2011. S. cephalus individuals ranging between I and VI years old were caught from Devres Stream. Studied individuals were between I and VI years old and their sex was determined as 51.67% male and 48.33% female. The fork length and body weight ranged from 8.79 – 19.64 cm and 9.73 – 126.60 g respectively. The von Bertalanffy growth equations were found: Lt = 27.163 [1 – e–0.159 (t+1.47)] for females and Lt = 27.078[1 – e–0.160 (t+1.46)] for males; Wt = 286.14 [1 – e–0.159 (t+1.47)]3.1049 for females and Wt = 284.43 [1 – e–0.160 (t+1.46)]2.9692 for males. The condition factor was calculated as 1.432 and 1.378 for females and males respectively.